Source locations of teleseismic P, SV, and SH waves observed in microseisms recorded by a large aperture seismic array in China - Liu, Qiaoxia; Koper, Keith D.; Burlacu, Relu; Ni, Sidao; Wang, Fuyun; Zou, Changqiao; Wei, Yunhao; Gal, Martin; Reading, Anya M. (Earth and planetary science letters, 2016)
Transversely polarized seismic waves are routinely observed in ambient seismic energy across a wide range of periods, however their origin is poorly understood because the corresponding source regions are either undefined or weakly constrained, and nearly all models of microseism generation incorporate a vertically oriented single force as the excitation mechanism. To better understand the origin of transversely polarized energy in the ambient seismic wavefield we make the first systematic attempt to locate the source regions of teleseismic SH waves observed in microseismic (2.5–20 s) noise. We focus on body waves instead of surface waves because the source regions can be constrained in both azimuth and distance using conventional array techniques. To locate microseismic sources of SH waves (as well as SV and P waves) we continuously backproject the vertical, radial, and transverse components of the ambient seismic wavefield recorded by a large-aperture array deployed in China during 2013–2014. As expected, persistent P wave sources are observed in the North Atlantic, North Pacific, and Indian Oceans, mainly at periods of 2.5–10 s, in regions with the strong ocean wave interactions needed to produce secondary microseisms. SV waves are commonly observed to originate from locations indistinguishable from the P wave sources, but with smaller signal-to-noise ratios. We also observe SH waves with about half or less the signal-to-noise ratio of SV waves. SH source regions are definitively located in deep water portions of the Pacific, away from the sloping continental shelves that are thought to be important for the generation of microseismic Love waves, but nearby regions that routinely generate teleseismic P waves. The excitation mechanism for the observed SH waves may therefore be related to the interaction of P waves with small-wavelength bathymetric features, such as seamounts and basins, through some sort of scattering process. •Teleseismic body waves (P, SV, SH) are observed in ambient noise recorded in China.•P waves have larger amplitude than SV waves, which are larger than SH waves.•P and SV waves originate from the same areas, SH waves from slightly different areas.